Lipid-modifying agents, from statins to PCSK9 inhibitors: JACC focus seminar - Preiss, D; Tobert, JA; Hovingh, GK; Reith, C (Elsevier, 2020)
Mendelian randomization studies and randomized trials have conclusively demonstrated that lower low-density lipoprotein (LDL) cholesterol results in fewer cardiovascular events. This review describes key stages in the evolution of LDL cholesterol–lowering treatment. Data from over 25 cardiovascular outcome trials confirm that, within a few years, statins lower the relative risk of major atherosclerotic events by about 22% per 38.7 mg/dl (1 mmol/l) reduction in LDL cholesterol, with similar benefit across patient subgroups. Meta-analyses of these trials have established the safety of statins with regard to nonvascular mortality and cancer. Other agents available for prescription include ezetimibe and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, which both reduce major atherosclerotic events in proportion to their effects on LDL cholesterol and have good safety profiles, though PCSK9 inhibitors remain costly. Investigational LDL cholesterol–lowering agents currently being tested in cardiovascular outcome studies are bempedoic acid, an adenosine triphosphate–citrate lyase inhibitor that reduces cholesterol synthesis, and inclisiran, a double-stranded small interfering ribonucleic acid that inhibits PCSK9 synthesis.